3‐Oxopyridazin‐5‐yl‐Chalcone Hybrids: Potent Antiplatelet Agents That Prevent Glycoprotein IIb/IIIa Activation. Issue 17 (19th June 2017) - Maatougui, Abdelaziz El; Yáñez, Matilde; Crespo, Abel; Fraiz, Nuria; Coelho, Alberto; Raviña, Enrique; Laguna, Reyes; Cano, Ernesto; Loza, María I.; Brea, José; Gutiérrez de Terán, Hugo; Sotelo, Eddy
Abstract: A novel family of potent and broad‐spectrum antiplatelet agents has been discovered by exploration of a library of 3‐oxopyridazin‐5‐yl‐chalcone hybrids. The pharmacological evaluation of the collection established the most salient features of the SAR in this series and allowed the identification of lead compounds that exhibit antiplatelet activity that is substantially superior to drugs in clinical use and 3, 4‐methylenedioxy‐β‐nitrostyrene (MNS). The derivatives reported herein act on GPIIb/IIIa, but in a different manner to classical antagonists (e. g., tirofiban), by preventing GPIIb/IIIa activation. Given their mechanism of action, these compounds might avoid the adverse effects of antagonists (paradoxical GPIIb/IIIa activation) and constitute attractive pharmacological tools for the development of tailored agents for the treatment of platelet‐dependent thrombosis. Abstract : A novel family of potent and broad‐spectrum antiplatelet agents has been discovered by exploration of a library of 3‐oxopyridazin‐5‐yl‐chalcone hybrids. Some of the identified compounds exhibit antiplatelet activity substantially superior to drugs in clinical use.